ENVIRONMENTAL AND MAN-MADE THREATS IN THE ZONE OF MILITARY CONFLICT IN EASTERN UKRAINE - Serhii Ivaniuta (Стратегічна панорама, 2018)
The inﬂuence of the military conﬂict in Eastern Ukraine on the increase of environmental and man-made threats is analyzed. The contemporary threats to the national security of Ukraine in the ﬁeld of environmental and manmade security which are strengthened as a result of military actions on the territory of antiterrorist operation are determined. Priority measures to improve monitoring and prevention of threats of environmental and technogenic origin in the zone of military conﬂict that could lead to negative consequences for the population and the environment in the case of their implementation are outlined.